Peran Event Marketing dalam Meningkatkan Brand Awareness dan Engagement pada IFBEX (International Franchise and Business Exchange) 2025 - Amanda Gracia Hamidah; Dewi Deniaty Sholihah (ManBiz: Journal of Management and Business, 2026)
This study analyzes the role of event marketing in increasing brand awareness and visitor engagement at IFBEX (International Franchise and Business Exchange) 2025, one of the largest business and franchise exhibitions in Indonesia. IFBEX features various activities such as brand showcases, business talks, workshops, and interactive activities designed to build rapport with exhibitors. Event marketing is considered capable of increasing exposure, expanding the market, and encouraging active interaction between brands and audiences. The study used a qualitative approach with a case study method through in-depth interviews with three internal informants from the IFBEX 2025 organizers involved in the planning, execution, and evaluation of the event. Data were obtained through interviews, direct observation during the event, and documentation in the form of insights into participant interactions at various event touchpoints. The study utilized Event Marketing theory with indicators of experiential value, interaction, and brand message delivery, as well as Keller's Brand Awareness and Engagement theory. The results showed that the IFBEX 2025 event marketing strategy successfully increased brand recall, strengthened attendees' direct experience with the brand, and encouraged active engagement through participatory activities. The study's conclusions confirm that event marketing has a significant impact on building awareness and engagement, particularly in the franchise industry, which requires an experiential and interactive approach.